Enhancing Humanistic and Spiritual Competence of Police Cadets Through Christian Education: A Community Outreach Program at SPN Polda North Sulawesi - Yessy Kenny Jacob (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2026)
This community outreach program aims to strengthen the humanistic and spiritual competence of Police Cadets at SPN Polda North Sulawesi through the integration of Christian Education principles. Police cadets often face emotionally challenging duties requiring empathy, moral integrity, and resilience. Christian values—particularly compassion, service, humility, and love—were applied as an educational framework to support cadets’ character development and social cohesion. The program consisted of interactive lectures, group reflections, and character-building sessions involving 200 police cadets from the 2023 DIKTUKBA cohort. Results indicate increased awareness of humanistic values, improved interpersonal communication, and enhanced spiritual readiness among cadets. This initiative demonstrates the relevance of Christian Education in strengthening moral and social capacities within law enforcement training institutions.